2017
DOI: 10.1186/s12931-017-0560-7
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting autophagy for prognosis based intervention of COPD-pathophysiology

Abstract: Chronic obstructive pulmonary disease (COPD) is foremost among the non-reversible fatal ailments where exposure to tobacco/biomass-smoke and aging are the major risk factors for the initiation and progression of the obstructive lung disease. The role of smoke-induced inflammatory-oxidative stress, apoptosis and cellular senescence in driving the alveolar damage that mediates the emphysema progression and severe lung function decline is apparent, although the central mechanism that regulates these processes was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 83 publications
(112 reference statements)
1
27
0
Order By: Relevance
“…The studies of Hussain and Sandri (21) and Plant et al (22) demonstrated that autophagy can affect the bronchial-muscle function of patients with COPD. The pathophysiological mechanisms involved in COPD, including oxidative stress and inflammation, are associated with autophagy (14,(23)(24)(25). Therefore, autophagy serves a role in the pathogenesis of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of Hussain and Sandri (21) and Plant et al (22) demonstrated that autophagy can affect the bronchial-muscle function of patients with COPD. The pathophysiological mechanisms involved in COPD, including oxidative stress and inflammation, are associated with autophagy (14,(23)(24)(25). Therefore, autophagy serves a role in the pathogenesis of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, alveolar emphysema is a primary cause of COPD and thus its early diagnosis may contribute to controlling this pathological condition. Recent evidence supports an important role for autophagy in the progression of COPD-emphysema [1,3,4]. Autophagy is an intracellular mechanism by which damaged cellular components and proteins are degraded and recycled by the cell itself as a defensive mechanism.…”
Section: Introductionmentioning
confidence: 97%
“…Previous publications have shown that fisetin has the ability to induce autophagy [ 15 , 18 , 19 , 22 ]; hence, we decided to investigate its effectiveness in recovering CS-impaired phagocytosis. However, it was first necessary to determine the dose of fisetin to be used for further experimentation; thus, by treating RAW264.7 cells with increasing doses of fisetin (0, 10, 20, and 40 ÎĽ M) for 8 hrs, we first selected the appropriate dose.…”
Section: Resultsmentioning
confidence: 99%
“…Fisetin is an over-the-counter dietary supplement that acts as an antioxidant for brain health [ 15 , 22 , 23 ]. In recent studies from our lab and others, fisetin has been shown to induce TFEB and consequentially autophagy [ 15 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%